The hazard of (sub)therapeutic doses of anticoagulants in non‐critically ill patients with Covid‐19: The Padua province experience. (24th August 2020) - Pesavento, Raffaele; Ceccato, Davide; Pasquetto, Giampaolo; Monticelli, Jacopo; Leone, Lucia; Frigo, Annachiara; Gorgi, Davide; Postal, Anna; Marchese, Giuseppe Maria; Cipriani, Alberto; Saller, Alois; Sarais, Cristiano; et al.
Abstract: Background: Coronavirus Disease 2019 (COVID‐19) is responsible for a worldwide pandemic, with a high rate of morbidity and mortality. The increasing evidence of an associated relevant prothrombotic coagulopathy has resulted in an increasing use of antithrombotic doses higher than usual in COVID‐19 patients. Information on the benefit/risk ratio of this approach is still lacking. Objective: To assess the incidence of relevant bleeding complications in association with the antithrombotic strategy and its relationship with the amount of drug. Methods: Consecutive COVID‐19 patients admitted between February and April 2020 were included in a retrospective analysis. Major bleedings (MB) and clinically relevant non‐major bleeding (CRNMB) were obtained from patient medical records and were adjudicated by an independent committee. Results: Of the 324 patients who were recruited, 240 had been treated with prophylactic doses and 84 with higher doses of anticoagulants. The rate of the composite endpoint of MB or CRNMB was 6.9 per 100‐person/months in patients who had been given prophylactic doses, and 26.4 per 100‐person/months in those who had been prescribed higher doses (hazard ratio, 3.89; 95% confidence interval, 1.90‐7.97). The corresponding rates for overall mortality were 12.2 and 20.1 per 100‐person/months, respectively. Conclusions: The rate of relevant bleeding events was high in patients treated with (sub)therapeutic doses of anticoagulants. In the latter group, overall mortality did not differ from that of patients treated with standard prophylactic doses and was even higher. Our result does not support a strategy of giving (sub)therapeutic doses of anticoagulants in non‐critically ill patients with COVID‐19.